Peer-Based Intervention in Improving Social Interaction of Autistic Children - Afifah, Aisyah Nisaul; Palem, Angela Elsani Dian; Bagis, Inayah Nisrin Salim; Mufadhilah, Nadia Diana Ummi; Novianti, Ranti (Department of Special Education, 2024)
This study is a literature review of peer-based interventions in improving social interaction in children with Autism Spectrum Disorder (ASD). Using a literature review approach, we searched for relevant literature to identify the effect of peer-based interventions in overcoming difficulties in children with Autism Spectrum Disorder (ASD) in their social interactions. The literature search was conducted through credible search engines such as Google Scholar, PubMed, and others. The search includes keywords such as